Construction of double-network hydrogel based on low methoxy pectin/polyvinyl alcohol and its structure and properties - Shen, Bihua; Zhang, Qiong; Zheng, Chenmin; Huang, Yufan; Zhang, Guoguang; Fei, Peng; Hu, Shirong (International journal of biological macromolecules, 2022)
In this study, an interpenetrating double-network hydrogel (LMP/AA/PVAH) was prepared based on low methoxy pectin (LMP), acrylic acid (AA) and polyvinyl alcohol (PVA). The first rigid network of chemical crosslinking was constructed via free radical polymerization of LMP and AA, and the second of ductile physical crosslinking network was constructed via cyclic freeze-thaw of PVA. The first cycle hardness and elasticity of the LMP/AA/PVAH significantly increased from 13.08 N and 0 to 24.28 N and 0.79, respectively, when the second network structure was constructed in the hydrogel by PVA. Besides, the PVA network might enhance the ductile and limit the swelling of hydrogel. In addition, the adsorption properties of LMP/AA/PVAH were evaluated by adsorption of methylene blue (MB). The adsorption behavior of MB by LMP/AA/PVAH conformed to the pseudo-second-order kinetic model. Besides, after 4 cycles of adsorption, there was no significant difference in adsorption capacity of LMP/AA/PVAH. The results showed that LMP/AA/PVAH had good reusability. [Display omitted] •It was constructed a double-network hydrogel based on low methoxy pectin.•The mechanical properties of double network hydrogel were significantly higher than that of single network hydrogel.•Hydrogel LMP/AA/PVAH had good repeatability.